1979
DOI: 10.3758/bf03335001
|View full text |Cite
|
Sign up to set email alerts
|

Similarity judgments of patterns and maps

Abstract: An algorithmic technique is described for generating from a common prototype three populations of forms (dots, open forms, and polygons) having different configurational properties. Within each population, subjects rated the similarity between standard stimuli and 20 transformations of these stimuli. The stimuli were represented to the subjects as abstract patterns or as maps. High rank·order correlations were obtained between the ratings given to the various transformations in each form population and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
1
8
0
Order By: Relevance
“…Inspection time was varied in a between-subject design. As in the Halpern et al (1979) study, it was found that the variables of form type (dots,lines, polygons) and axis of rotation (x, y, z) had no effect on perceived similarity in the long exposure conditions. However, when inspection time was limited to 150 msec, both variables had a substantial impact.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…Inspection time was varied in a between-subject design. As in the Halpern et al (1979) study, it was found that the variables of form type (dots,lines, polygons) and axis of rotation (x, y, z) had no effect on perceived similarity in the long exposure conditions. However, when inspection time was limited to 150 msec, both variables had a substantial impact.…”
mentioning
confidence: 52%
“…More specifically, at very short exposures (150 msec), which are rarely used in ratings studies, perceived similarity is very sensitive to variables that have no effect at longer exposures. This finding undermines the common practice of selecting stimuli for use in reaction time and other experiments with brief exposure durations on the basis of similarity ratings gathered under free inspection conditions.The stimulus patterns we used were taken from a study by Halpern, Fishbein, and Warm (1979) and are shown in Figure 1. These investigators were interested in the problem of representativeness in the perceived similarity of patterns.…”
mentioning
confidence: 99%
See 3 more Smart Citations